On Pata Convex-Type Contractive Mappings. (8th September 2022) - Aktay, Merve; Özdemir, Murat
Abstract : In this work, we introduce weak Pata convex contractions and weak E -Pata convex contractions via simulation functions in metric spaces to prove some fixed point results for such mappings. Also, we consider an example related to weak Pata convex contractions. Consequently, our results generalize and unify some results in the literature.